2022
DOI: 10.3390/s22030791
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Methods of Surface Texture Characterisation for Reduction of the Frequency-Based Errors in the Measurement and Data Analysis Processes

Abstract: Processes of surface texture characterisation can be roughly divided into measurement issues and analysis of the results obtained. Both actions can be fraught with various errors, some of which can be analysed with frequency performance. In this paper, various types of surface topographies were studied, e.g., cylinder liners after the plateau-honing process, plateau-honed liners with additionally burnished dimples of various sizes (width and depth), turned, milled, ground, laser-textured, ceramic, composite an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Holes, dimples, scratches, or other non-high-frequency-noise features (shortly non-noise features), represent frequencies in a different domain than a high-frequency spectrum. It was also previously indicated that the occurrence of non-noise features caused NS was not isotropic [16]. Therefore, both properties require the NS to be in the high-frequency domain and isotropic.…”
Section: Selection Of Cut-off Value With a Feature-based Techniquementioning
confidence: 96%
See 1 more Smart Citation
“…Holes, dimples, scratches, or other non-high-frequency-noise features (shortly non-noise features), represent frequencies in a different domain than a high-frequency spectrum. It was also previously indicated that the occurrence of non-noise features caused NS was not isotropic [16]. Therefore, both properties require the NS to be in the high-frequency domain and isotropic.…”
Section: Selection Of Cut-off Value With a Feature-based Techniquementioning
confidence: 96%
“…However, the measurement noise in the high-frequency domain [15] is studied in the present analysis. Generally, in the non-contact (optical) measurement of surface (topography), according to the non-uniform distribution of the light intensity, the received signal is susceptible to being skewed and asymmetric; therefore, a lot of high-frequency noise can be included [16]. Seeking the source, high-frequency noise can be caused by the mechanics' instability, considering any influences from the environment, but, in most cases, this type of error is the result of vibration [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Different conditions for the implementation of sheet metal forming processes and the variety of plastically processed materials mean that the following parameters should be taken into account when selecting a lubricant for a specific application [ 11 ]: processing temperature, value of maximum unit pressures, grade of processed material and grade of tool material, sliding speed, type of protective coating on the tool surface, and tool design. The surface topography of sheet metal has a decisive influence on friction, wear, and lubrication under mixed lubrication and dry friction conditions [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Precise studies of the LST surface topography measurement process can influence the tribological performance applications like friction [ 15 ], sealing [ 16 ], lubricant retention [ 17 ], wear [ 18 ] or wear resistance [ 19 ], corrosion [ 20 ], fatigue [ 21 ] or, generally, material contact [ 22 ] and material properties. In general, the surface topography analysis can be roughly divided into measurement and data analysis processes [ 23 ]. Each part of the surface topography study, simultaneously, can be fraught with many factors influencing the accuracy of the analysis.…”
Section: Introductionmentioning
confidence: 99%